Problematika dan Efektivitas Penerapan Problem Based Learning (PBL) dalam Pembelajaran Pendidikan Agama Islam di MAN 01 Kotabumi - Alfira Mersania Shintia; Fidari Nur Dini; Citra Ayu Hidayah; Julmi J (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the problems and effectiveness of implementing Problem Based Learning (PBL) in Islamic Religious Education (PAI) learning at MAN 01 Kotabumi. The urgency of this research lies in the persistent gap between PBL's theoretical promise and its practical execution in Islamic school contexts, particularly in regions with limited infrastructure. Using a mixed-methods approach, data were collected through classroom observation, structured interviews with five PAI teachers, student questionnaires (n=120), and documentary analysis of learning outcomes over two academic semesters. Quantitative data were analyzed using descriptive statistics and independent t-tests, while qualitative data underwent thematic analysis. Findings reveal that student learning outcomes improved significantly (mean pre-test = 68.4; mean post-test = 81.7; t = 9.23; p < 0.001) when PBL was applied. However, five core problems were identified: (1) limited teacher readiness in constructing contextual problem scenarios, (2) time constraints in curriculum pacing, (3) inadequate digital infrastructure, (4) heterogeneous student prior knowledge, and (5) inconsistency in authentic assessment practices. The novelty of this research lies in its dual-focus framework that simultaneously maps the problematic dimensions and effectiveness indicators of PBL within PAI, providing an evidence-based model for Islamic school practitioners. This study contributes an original typology of PBL constraints specific to madrasah environments and recommends a contextual PBL adaptation protocol.